Effect of different doses of probiotics on growth performance of New Hampshire chicken - Pandey, Luma Nidhi; Chaudhary, Jagbir; Shah, Manoj Kumar (Journal of Agriculture and Natural Resources, 2022)
The feed additive is one of the important components in poultry production to enhance the performance of birds. An experiment was conducted atNational Animal Nutrition Research Center, Khumaltar, Lalitpur, Nepal in order to evaluate the feasibility of probiotics as feed additives in New Hampshire chicken performance. The experiment was laid out with four treatments viz. basal diet which is concentrate mixture without inclusion of probiotic (Lactobacillus acidophilus - 50*109 cfu/kg, Bacillus subtilis - 1*109 cfu/kg, Bacillus licheniformis - 1*109 cfu/kg, Saccharomyces boulardii - 10*109cfu/kg) as basal diet with 0.5 gram of probiotic per liter of water , basal diet with 1 gram of probiotics per liter of water and basal diet with 1.5 gram of probiotics per liter of water under completely randomized design replicated three times. A total of 180, 8th week New Hampshire chickens were allotted with 15 birds in each experimental unit. Experimental birds were fed ad-libitum amount of formulated concentrate feed and clean drinking water with proper management practices.The highest weight gain was observed in treatment group provided with 1g of probiotic in diet (1957.96 g) followed by treatment group provided with 0.5 g of probiotic in diet (1891.40 g), 1.5g probiotic in diet (1879 g) and lowest in treatment group without probiotic in diet (1793.62 g). However there was no significant difference in total feed intake between all the treatment groups. Similarly, better feed conversion ratio (FCR) was found inbirds fed with 1g probiotic (3.59) followed by 0.5g probiotic (3.67), 1.5 g probiotic (3.72) and without probiotic in diet (3.87). Dressing percentage was also found higher (85.03 %) in birds fed with 1g of probiotic included diet than other groups of birds.